The Analysis of Added Value of Duck Egg Processing (Case Study in Home Industry Usaha Baru Telur Asin) - Sitti Hadijah; Azhar Bafadal; Munirwan Zani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Agroindustry is an industrial activity that utilizes agricultural products as raw materials to be processed into new products. Home industry Usaha Baru Telur Asin is a business that processes duck eggs into salted egg products, which use tools and processing technology in their activities. With the help of technology, there will be a transformation of raw materials (duck eggs), which are of lower value, into products (salted eggs) of high value. This study aims to analyze the amount of added value generated from duck egg processing and the remuneration received by workers and agro-industrial processors in the home industry of the Usaha Baru Telur Asin in Lapulu Village, Abeli ​​District. The data collection for this research was carried out in May-August 2022. The location of this research was determined purposively. Namely, the selection was intentional because, in the Village, there is a business processing duck eggs into salted eggs. Respondents to this study were business owners and workers in the